Vitamin D receptor expression levels determine the severity and complexity of disease progression among leprosy reaction patients. (July 2015) - Mandal, D.; Reja, A.H.H.; Biswas, N.; Bhattacharyya, P.; Patra, P.K.; Bhattacharya, B.
Abstract: We studied the roles of vitamin D and its receptor, VDR, in the progression of leprosy. The majority of individuals with leprosy from Kolkata, India, with a type 1 or type 2 reaction have low levels of vitamin D3 in serum samples. Interestingly, individuals with a type 2 reaction associated with neuritis/erythema nodosum leprosum had very low VDR mRNA expression levels, ranging from 5% to 10%, compared to that of healthy control subjects; these patients also had a high bacilli index, ranging from 3+ to 5+. This is the first report to indicate that VDR expression levels may determine the complexity and severity of the progression of leprosy.